Artificial Intelligence in Identifying Patients With Undiagnosed Nonalcoholic Steatohepatitis - Onur Baser; Gabriela Samayoa; Nehir Yapar; Erdem Baser (Journal of Health Economics and Outcomes Research)
**Background:** Although increasing in prevalence, nonalcoholic steatohepatitis (NASH) is often undiagnosed in clinical practice.